Understanding the evolution of trust in a participatory health research partnership: A qualitative study - Meghan Gilfoyle; Anne MacFarlane; Zoe Hughes; Jon Salsberg (Wiley, 2024)
Abstract Introduction Advancements in evaluating the impact of participatory health research (PHR) have been made through comprehensive models like the community‐based participatory research (CBPR) conceptual model, which provides a useful framework for exploring how context and partnership processes can influence health research design and interventions. However, challenges in operationalising aspects of the model limit our understanding and evaluation of the PHR process. Trust is frequently identified as an important component of the CBPR model, which supports the development of key partnership outcomes, such as partnership synergy. However, trust continues to be limited to a binary view (as present or absent), which is problematic given its inherently dynamic and temporal nature. Study Aim The aim of this qualitative study is to understand the evolution of trust in the national public and patient involvement (PPI) network in Ireland. Setting and Participants Participants from the PPI network (n = 15/21) completed a semistructured interview discussing the evolution of trust by reviewing four social network maps derived from a previous longitudinal study. Analysis Following Braun and Clarke, we used reflexive thematic analysis, to iteratively develop, analyse and interpret our mediated reflection of the data. Results Participants described the evolution of trust as a function of three contextual factors: (1) the set‐up and organisation of the network, (2) how people work together and (3) reflection on the process and outcomes. Their descriptions across these themes seemed to vary depending on partnership type with National Partners and Site Leads having more opportunities to demonstrate trust (e.g., via leadership roles or more resources), compared to Local. Thus, visibility and the opportunity to be visible, depending on the set‐up and organisation of the network and how people work together, seemingly play an important role in the evolution of trust over time. Based on these findings, we provide important questions for reflection across themes that could be considered for future PHR partnerships. Discussion Given that the opportunity and visibility to build and maintain trust over time may not be equally available to all partners, it is important to find ways to invest in and commit to equitable relationships as the key to the success (i.e., longevity) of partnerships. We reflect on/offer important implications for those engaging in PHR partnerships and those who fund such research. Patient or Public Contribution A Research Advisory Group comprising four research partners (representing academic, service and community organisations) from the PPI Ignite Network provided input and approval for the research objectives of this study as well as previously published work informing this study. Informal consultation occurred with members of this group to discuss findings from this study, assisting with the way findings are presented and described, to be accessible for diverse audiences. Two Research Advisory Group members were involved in the interpretation of the results, and one is a co‐author of this manuscript (Zoe Hughes).